Collaborative Governance In Gender Mainstreaming Policy In Yogyakarta City - MUHAMMAD AMMAR HIDAYAHTULLOH; AMALIA NURUL HUTAMI (Jurnal Studi Pemerintahan, 2019)
Gender mainstreaming becomes the global strategy used in realizing gender equality as one of the sustainable development goals that are envisioned to be accomplished by 2030. Indonesia as a part of the international community is fully committed to adopting gender mainstreaming in the national development plan for the last two decades. Through the Presidential Decree No. 9 of 2000, the local government is mandated to mainstreaming gender in the development program. Yogyakarta city has progressively implemented gender mainstreaming policy in development indicated by its high percentage of Gender Development Index (GDI) of 98.26% in 2017. As a matter of fact, Yogyakarta was also awarded the Anugerah Parahita Ekapraya (APE) by the Ministry of Women’s Empowerment and Child Protection (MoWECP) for its commitment towards gender equality and women empowerment. This research is an exemplary study to analyze the collaborative governance in the gender mainstreaming strategy in Yogyakarta city. The method used in this research is a qualitative method using primary data by conducting an interview and secondary data such as books, articles, official documents, and journals. The authors use the collaborative governance concept by Ansell and Gash, as well as the twin-track gender mainstreaming model by Moser as the theoretical frameworks. The authors signify that the Government of Yogyakarta city has carried out a collaboration with the other stakeholders such as civil societies and private sectors in the gender mainstreaming strategy in Yogyakarta in a limited manner.